Peran Perangkat Desa dalam Menjaga Stabilitas Sosial dan Memberikan Pelayanan Publik di Desa Jubung - Fatiya Diana Wulandari Putri; Angella Yunita Azarah; Rahmasari Dwi Agustina (Pusat Riset dan Inovasi Nasional, 2023)
Jubung Village is a rural community located in Sukorambi Prefecture, Jember District. The research emphasizes the importance of the role of village devices inining social stability and providing public services in Jubung Village. The village system plays a crucial role in managing the governance of the village and improving the well-being of the community. However, they also face challenges and complexities in carrying out their duties and functions. In the village development perspective, the role of the village device becomes a key element in achieving the goals of sustainable development. This study uses the structural theory of functionalism proposed by Talcott Parsons. Society is seen by this theory as a system of interrelated parts to stability and balance. The purpose of this research is to find out how the role of village devices inining social stability and providing public service in Jubung Village. This type of research is qualitative descriptive research. The results of this research show that the Jubung Village device performs its role inining social stability and providing public service well.